2020
DOI: 10.1111/bjh.17142
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral prophylaxis for hepatitis B carriers improves the prognosis of diffuse large B‐cell lymphoma in Taiwan – a population‐based study

Abstract: The prevention of hepatitis B virus (HBV) reactivation during rituximab treatment for diffuse large B-cell lymphoma (DLBCL) is important in the HBV-endemic area. This population-based study examines the impact of antiviral prophylaxis for DLBCL patients with HBV infections. We identified 3702 adult patients with newly diagnosed DLBCL between 2011 and 2015 receiving R-CHOP, R-CVP, CHOP or CVP from the Taiwan Cancer Registry. We further stratified them into three groups: HBsAg-negative patients (HBV-negative, N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
1
11
1
Order By: Relevance
“…To our knowledge, this is one of the few studies to examine whether the presence of HBV infection affected the clinical characteristics and outcomes in patients with DLBCL, our study included 127 HBsAg-positive patients, which was one of the largest number of patients in all studies of this disease. In our study, HBV prevalence in DLBCL patients was approximately 30.2%, which was similar or higher than the 13.3%–30.9% observed in previous studies from China, Taiwan, Singapore, and another Asian country [ 9 , 11 , 24 , 29 , 31 , 33 – 35 ]. These results suggested that in HBV-prevalent regions, a certain percentage of DLBCL patients are chronically infected with HBV.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…To our knowledge, this is one of the few studies to examine whether the presence of HBV infection affected the clinical characteristics and outcomes in patients with DLBCL, our study included 127 HBsAg-positive patients, which was one of the largest number of patients in all studies of this disease. In our study, HBV prevalence in DLBCL patients was approximately 30.2%, which was similar or higher than the 13.3%–30.9% observed in previous studies from China, Taiwan, Singapore, and another Asian country [ 9 , 11 , 24 , 29 , 31 , 33 – 35 ]. These results suggested that in HBV-prevalent regions, a certain percentage of DLBCL patients are chronically infected with HBV.…”
Section: Discussionsupporting
confidence: 85%
“…The latest report by Huang et al displayed that the mOS of HBV-negative and HBV carriers who received antiviral prophylaxis was similar. However, the mOS of HBV carriers who did not receive antiviral prophylaxis was significantly shorter than HBV carriers who received antiviral prophylaxis, indicating that antiviral prophylaxis improves OS in HBsAg-positive DLBCL patients [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, patients with DLBCL and active HBV infection had similar outcomes to uninfected patients when they received immunochemotherapy and antivirals. A population-based study ( 24 ) indicated those patients with DLBCL and HBV infection had comparable survival outcome than those without HBV infection (median OS, not reached vs. 74.23 months, respectively) when antiviral prophylaxis was used. Another study ( 25 ) compared the treatment responses and survival between 116 patients with HBsAg-positive DLBCL and 278 patients with HBsAg-negative DLBCL, all of whom received rituximab-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoma is a primary malignant tumor of lymph nodes or lymph tissues, and its occurrence may be related to gene mutations (Zahn et al, 2020), virus and other pathogen infections (Huang et al, 2021). Studies highlight the roles of clonally diverse CD4 T cells and innate effectors in the efficacy of PD-1 blockade in classical Hodgkin lymphomas (Cader et al, 2020).…”
Section: Lymphomamentioning
confidence: 99%